Penurunan Daya Beli di Indonesia Periode 2012 - 2017 dan Dampaknya Terhadap Harga Saham Perusahaan Ritel Go Publik - Erni Prasetiyani; Sukarni Novitasari (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
Declining purchasing power in several retail outlets that occurred in 2017 indicates a change in consumer behavior. This study discusses an indication of a decrease in purchasing power and its effect on stock prices in 6 retail companies that have go public based on financial reports issued by the Indonesia Stock Exchange or www.idx.co.id using financial statement analysis using the ratio of Total Asset Turn Over (TATO) , Return on Equity (ROE), Return on Investment (ROI), Inventory Turn Over (ITO), Average Day Inventory (ADI) as independent variables and Market to Book Value (MBV) as the dependent variable. Data is processed using Linear Regression Data Panel. The results of the hypotheses of the five ratios which are made as independent variables are only TATO, ROE and ROI which partially affect MBV